Oxygen therapy devices and portable ventilators for improved physical activity in daily life in patients with chronic respiratory disease. (1st February 2017) - Furlanetto, Karina Couto; Pitta, Fabio
ABSTRACT: Introduction : Patients with hypoxemia and chronic respiratory failure may need to use oxygen therapy to correct hypoxemia and to use ventilatory support to augment alveolar ventilation, reverse abnormalities in blood gases (in particular hypercapnia) and reduce the work of breathing. Areas covered : This narrative review provides an overview on the use of oxygen therapy devices or portable ventilators for improved physical activity in daily life (PADL) as well as discusses the issue of lower mobility in daily life among stable patients with chronic respiratory disease who present indication for long-term oxygen therapy (LTOT) or home-based noninvasive ventilation (NIV). A literature review of these concepts was performed by using all related search terms. Expert commentary : Technological advances led to the development of light and small oxygen therapy devices and portable ventilators which aim to facilitate patients' mobility and ambulation. However, the day-by-day dependence of a device may reduce mobility and partially impair patients' PADL. Nocturnal NIV implementation in hypercapnic patients seems promising to improve PADL. The magnitude of their equipment-related physical inactivity is underexplored up to this moment and more long-term randomized clinical trials and meta-analysis examining the effects of ambulatory oxygen and NIV on PADL are required.